Growth Strategy of New Business Ventures: Characteristics of South East Europe Entrepreneurs - Leković, Bojan; Petrović, Miodrag; Bobera, Dušan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The research area in this paper is the determinants of the impact on the growth of entrepreneurial ventures found during the incubation period. The research covered the following determinants: entrepreneurial knowledge and skills, entrepreneurial motivation, and technological orientation of entrepreneurs. The data for research purposes were collected from the Global Entrepreneurship Monitor (GEM) database. The research sample contains data on entrepreneurs who have started business in Southeast Europe. The methodology of empirical research consists of Logit regression and the concept of marginal effect. Research findings indicate that early-stage entrepreneurs are guided by a motive for greater independence. Also, the mentioned group of entrepreneurs possesses adequate knowledge and skills and use new technologies in their business. The analysis of the orientation on the growth of entrepreneurs at the national level also revealed significant differences between the countries of Southeast Europe.